Elevated RBP4 in Subclinical Ketosis Cows Inhibits Follicular Granulosa Cell Proliferation and Steroid Hormone Synthesis - Chang Zhao; Ruru Xu; Weizhe Yan; Benzheng Jiang; Shibin Feng; Xichun Wang; Hongyan Ding (Animals)
The mechanism by which subclinical ketosis (SCK) causes postpartum reproductive disorders in dairy cows remains unclear. In this study, cows within the day 14 to 21 postpartum period were categorized into the SCK group or the control group. Subsequently, they were monitored until 45 d to 60 d postpartum and divided into the SCK anestrus group (SCK-AE, n = 12) and the control estrus group (C-E, n = 12). In comparison to the C-E group, the RBP4 and p-AKT of the SCK-AE group exhibited increased levels in serum, liver, and ovaries. In the in vitro experimental cultivation of granulosa cells (GCs), after adding RBP4, cell proliferation, steroid hormone secretion and synthesis, and GLUT4 secretion were inhibited, and cell apoptosis was exacerbated. After silencing STRA6 (RBP4 receptor), cell proliferation and steroid hormone secretion and synthesis, as well as the inhibition of GLUT4, were alleviated, and the situation of cell apoptosis also improved. The SC79 activator could promote the phosphorylation of AKT, thus alleviating the increased cell proliferation, steroid hormone secretion and synthesis, GLUT4 inhibition, and apoptosis rate in cow GCs induced by RBP4 stimulation. Our research indicates that elevated RBP4 levels in SCK cows inhibit the proliferation, apoptosis, and steroid hormone synthesis of GCs through the STRA6 receptor and the PI3K/AKT pathway.